Focal Cortical Dysplasia - Crino, Peter B. (Seminars in Neurology, 2015)
Focal cortical dysplasias are common malformations of cerebral cortical development and are highly associated with medically intractable epilepsy. They have been classified into neuropathological subtypes (type Ia, Ib, IIa, IIb, and III) based on the severity of cytoarchitectural disruption—tangential or radial dispersion, or loss of laminar structure—and the presence of unique cells types such as cytomegalic neurons or balloon cells. Most focal cortical dysplasias can be identified on neuroimaging and many require resective epilepsy surgery to cure refractory seizures. The pathogenesis of focal cortical dysplasias remains to be defined, although there is recent evidence to suggest that focal cortical dysplasias arise from de novo somatic mutations occurring during brain development. Some focal cortical dysplasia subtypes show a link to the mammalian target of rapamycin signaling cascade; this has now extended to other cortical malformations, including hemimegalencephaly.
Keywords: cortical dysplasia; mTOR; tuberous sclerosis